KEMAMPUAN MAHASISWA SEMESTER IV PROGRAM STUDI PENDIDIKAN BAHASA, SASTRA INDONESIA DAN DAERAH MEMBEDAKAN KATA MAJEMUK DAN FRASA - Awalludin, Awalludin (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The aim of this research is (1) to describe the ability of fourth semester students of Language Education Program, Indonesian and Regional Literature to distinguish compounds and phrases and (2) to describe students difficulties in differentiating compound words and phrases. The method used in this research is descriptive method. Data collection techniques in this study using written test and questionnaires. Data analysis technique used is descriptive analysis technique. The result of the analysis of written test showed that the students who got the value of ≥ 80 and above or predicate very good amounted to 18 people (40.90%), students who scored 70-79 or got the good rating category there were 5 people (11.38% , students who got the score of 56-69 or got the predicate of appraisal enough able to have 17 people (38,63%), student who get score 40-55 or get predicate of insufficient assessment there are 4 people (9,09%), student gets the value of ≤ 40 or below or get the rating predicate failed there are 0 people (0%). Based on the above description can be seen that the students who got the value of ≥ 70 and above as many as 23 people (52.28%), while those who declared not able or got ≤ 70 less as many as 21 people (47.72%). So, the fourth semester students of Language Education Program, Indonesian Literature, and Region are able to differentiate compound words and phrases.